DEVELOPING WEB-BASED LEARNING MEDIA USING DREAMWEAVER CS4 APPLICATIONS ON THE SUBJECT OF SET FOR STUDENTS CLASS VII OF SMP - Feni Lusiana; Uus Kusdinar (Universitas Ahmad Dahlan, 2017)
Developments of technology, communications, and information are growing very fast to get easy to looking for and get the information in all sectors. One of the sectors that get a good impact is aducation. By using learning media can help the students to understand math. This research is the development that has a purpose to produce the products of Developing web-based learning media using Dreamweaver CS4 application on the subject of the set for students class VII of SMP that can be used in the teaching-learning process of math. The model development of learning media using ADDIE, are analysis, design, development, implementation, and evaluation. The subjects of the study include subject matter experts, media experts, and the seventh-grade students of SMP Muhammadiyah Magelang Tempuran. Techniques of data collection was done by questionnaire. Technical analysis of the data in this study conducted quantitatively converted into qualitative values Likert scale. The results of this development research is a learning website that address in mathscience .web.id. Â To know the results of the test in the subject of media can be a score of 91.5 with very good categories, from media test score of 88.5 in very good categories, and from the students respond a score of 78.8 in the very good category. However, the web-based learning media development on the subject of compilation include in the good category, so it can be used as learning media in math.